Primary murine high-grade glioma cells derived from RCAS/tv-a diffuse glioma model reprogram naive T cells into immunosuppressive regulatory T lymphocytes - Alessandro Canella; Mykyta Artomov; Aleksandr Ukhatov; Sakthi Rajendran; Phillip Perez; Uksha Saini; Jack Hedberg; Kevin Cassady; Prajwal Rajappa (Molecular Therapy: Oncology)
High-grade gliomas (HGGs) and glioblastomas (GBMs) are the most aggressive and lethal brain tumors. The current standard of care (SOC) includes gross safe surgical resection followed by chemoradiotherapy. The main chemotherapeutic agents are the DNA-alkylating agent temozolomide (TMZ) and adjuvants. Due to the outdated therapeutic protocols and lack of specific treatments, there is an urgent and rising need to improve our understanding of tumor biology and design more effective therapeutic strategies. In vitro models are essential for investigating glioma biology and testing novel therapeutic approaches. While using commercially available and patient-derived glioma cell lines for in vitro studies is common practice, they exhibit several limitations, including failing to maintain the genetic and phenotypic diversity of primary tumors, undergo genetic drift over time, and often lacking the invasive and stem-like characteristics of patient tumors. These limitations can lead to inconsistent and non-reproducible results, hampering translational research progress. In this study, we established a novel primary murine HGG cell line, isolated from an immunocompetent HGG-bearing RCAS/T-va mouse. We characterized the transcriptome and phenotype to ensure that this cell line resembles the nature of HGGs and retains the ability to reprogram primary murine T lymphocytes.